2003
DOI: 10.1097/00126334-200304010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Recent HIV Infections Using the Avidity Index and an Automated Enzyme Immunoassay

Abstract: We evaluated a procedure for identifying recent HIV infections, using sequential serum samples from 47 HIV-positive persons for whom the seroconversion date could be accurately estimated. Each serum sample was divided into two aliquots: one diluted with phosphate-buffered saline and the other diluted with 1 M guanidine. We assayed the aliquots with the automated AxSYM HIV1/2gO test (Abbott Diagnostics Division), without modifying the manufacturer's protocol. We then calculated the avidity index (AI): the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 9 publications
1
80
1
2
Order By: Relevance
“…The avidity index [AI], determined as the ratio of the sample/cut-off value for the guanidine aliquot to that of the phosphate-buffered saline aliquot, was calculated based on serum samples with well documented dates of HIV infection, showed that the mean AIs were 0.68±0.16, within 6 months of infection, and 0.98±0.10 after 6 months. An AI of < 0.90 correctly identified 88.2% of recent infec-tions, but misclassified as recent infections 13.2% of serum samples collected afterward 33 . Avidity indices of ≤ 0.75 and ≤ 0.80 consistently identified seroconversion within 125 (95%CI: 85-164) and 142 (95%CI, 101-183) days, respectively 34 .…”
Section: Avidity Index Methods •mentioning
confidence: 97%
See 1 more Smart Citation
“…The avidity index [AI], determined as the ratio of the sample/cut-off value for the guanidine aliquot to that of the phosphate-buffered saline aliquot, was calculated based on serum samples with well documented dates of HIV infection, showed that the mean AIs were 0.68±0.16, within 6 months of infection, and 0.98±0.10 after 6 months. An AI of < 0.90 correctly identified 88.2% of recent infec-tions, but misclassified as recent infections 13.2% of serum samples collected afterward 33 . Avidity indices of ≤ 0.75 and ≤ 0.80 consistently identified seroconversion within 125 (95%CI: 85-164) and 142 (95%CI, 101-183) days, respectively 34 .…”
Section: Avidity Index Methods •mentioning
confidence: 97%
“…Differences in the IgG avidity to HIV-1 antigens have been described as a useful tool to discriminate recent from long-term HIV-1 infections 31,32,33 . In order to measure the differences on IgG avidity, a commercial method used for HIV diagnostic (AxSYM HIV1/2gO test; Abbott) was modified and the serum samples were tested in parallel diluted in phosphate-buffered saline and in 1 M guanidine.…”
Section: Avidity Index Methods •mentioning
confidence: 99%
“…Nei soggetti con infezione recente, che presentano principalmente anticorpi a bassa avidità, l'intensità del segnale emesso dall'aliquota trattata con guanidina risulta inferiore rispetto all'aliquota non trattata poiché tale agente rompe i legami deboli che si creano tra anticorpi a bassa avidità ed antigene. Il rapporto tra il segnale dell'aliquota con la guanidina e quello dell'aliquota con il tampone viene espresso come "indice di avidità" (AI), il cui valore aumenta progressivamente nel tempo con l'aumentare della maturazione degli anticorpi e raggiunge un "plateau" entro il primo anno dalla sieroconversione (13,14). Analisi statistica La differenza tra medie è stata analizzata con il test t di Student.…”
Section: Materiali E Metodiunclassified
“…Una "datazione" dell'infezione, utile sia per scopi epidemiologici (sorveglianza di infezione, incidenza) che clinici è teoricamente possibile, come per altre patologie infettive, con metodiche atte a valutare l'avidità anticorpale, in base al principio ormai assodato del progressivo incremento della medesima nei mesi successivi all'infezione primaria e della persistenza di un'avidità anticorpale elevata nelle infezioni croniche (4). Il nostro gruppo di lavoro, con la collaborazione di esperti nel settore diagnostico e immunologico, ha messo a punto un test su siero che, valutando l'avidità degli anticorpi anti-HIV su sieri con positività anticorpale confermata, identifica le infezioni recenti (<6 mesi dall'infezione) con buona accuratezza (13,14). L'AI ha il vantaggio, rispetto ad altri metodi studiati per lo stesso scopo (10), di presentarsi come variabile continua consentendo così di poter scegliere diversi valori soglia a seconda dell'obiettivo prestabilito, in modo da privilegiare la sensibilità ovvero la specificità del test.…”
Section: Introduzioneunclassified
“…Antibody avidity assays quantify the avidity (binding strength) of anti-HIV antibodies in serum or plasma to HIV antigen. [6][7][8][9] Antibody avidity usually increases with duration of infection. People with recent HIV infection (e.g., infected for <6 months) tend to have low antibody avidity.…”
mentioning
confidence: 99%